Preparation of Biocomposite Material with Superhydrophobic Surface by Reinforcing Waste Polypropylene with Sisal (Agave sisalana) Fibers - Seyoum Getaneh Abebayehu; Adam Mekonnen Engida (International Journal of Polymer Science)
Nowadays, eco-friendly, renewable, and biodegradable biocomposites are among the most intensely sought materials of choice. Biocomposites have been widely used as substitutes for plastics due to their biodegradability. However, biocomposite materials absorb water and ultimately loss mechanical properties that affect service life. In this work, a biocomposite material with superhydrophobic surface was prepared by reinforcing waste polypropylene with sisal (Agave sisalana) fibers. The biocomposite was prepared by mixing waste polypropylene and sisal fiber with 5%, 10%, 15%, and 20% fiber loading. Based on characterization results, the composite with 15% fiber content is considered as optimum ratio. Physicochemical properties of composites were evaluated using standard American Society of Testing Materials including biodegradability test and chemical resistance test. The biodegradability of the composite before surface modification was determined by calculating weight loss and found to be 0.11%, 4.62%, 7.15%, and 10.97% for 0%, 5%, 10%, and 15% fiber loadings, and their tensile strength was 10.25±0.05, 14.47±0.02, 14.48±0.02, and 19.90±0.09 MPa for 0%, 5%, 10%, and 15% fiber content, respectively. The surface of the composite was modified for hydrophobicity by etching the surface with chromic acid followed by treating with stearic acid. The FTIR and the SEM images of unmodified and modified (superhydrophobic) surface of composites clearly state the significant difference in chemical composition and surface structure, respectively. The superhydrophobicity of the surface-modified biocomposite was defined by its self-cleaning and low wet ability properties.